1995
DOI: 10.1111/j.1479-828x.1995.tb02155.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study of Prostaglandin 15‐Methyl F2 alpha Compared With Syntometrine for Prophylactic Use in the Third Stage of Labour

Abstract: A randomized controlled study of 112 women with singleton pregnancies at term, and no antenatal complications, admitted in spontaneous labour were randomized to receive either an intramuscular injection of 0.5 mg of Syntometrine or an intramuscular injection of 125 ug of prostaglandin 15-methyl F2 alpha at delivery of the anterior shoulder of the baby. Blood lost in the first 2 hours, and subsequent 22 hours postdelivery were collected separately and measured by colourimetric measurement of haemoglobin content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
1
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
(5 reference statements)
5
1
0
Order By: Relevance
“…Tachycardia was observed in 36% patients which were attributed to increased blood loss in this group. This is comparable to the study of Chua S et al (1995) where they found a significant increase in the incidence of diarrhea with prostidin. 12 In group D, minor side effects, like shivering and fever, were present in 48% and 56% of patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Tachycardia was observed in 36% patients which were attributed to increased blood loss in this group. This is comparable to the study of Chua S et al (1995) where they found a significant increase in the incidence of diarrhea with prostidin. 12 In group D, minor side effects, like shivering and fever, were present in 48% and 56% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…This is comparable to the study of Chua S et al (1995) where they found a significant increase in the incidence of diarrhea with prostidin. 12 In group D, minor side effects, like shivering and fever, were present in 48% and 56% of patients. Our study is consistent with the study of El Refaey et al (1997), Hofmeyer GJ et al (1998), F Amant et al (1999), Hazem El-Rafaey et al (2000) in which their patients also exhibited fever and shivering.…”
Section: Discussionsupporting
confidence: 90%
“…In group D, minor side effects, like shivering and fever, were present in 48% and 56% of patients. Our study is consistent with the study of El Refaey et al (1997), Hofmeyer G J et al (1998), F Amant et al (1999), Hazem El-Rafaey et al (2000) in which their patients also exhibited fever and shivering [22,23,25].…”
Section: Original Research Articlesupporting
confidence: 93%
“…In group B Diarrhea and vomiting were most commonly observed inalong with chills in only 12%. This is comparable to the study of Chua S et al (1995) where they found a significant increase in the incidence of diarrhea with prostidin [24].…”
Section: Original Research Articlesupporting
confidence: 84%
“…6 In the present study mean duration of third stage of labour was 5.03±1.9 minutes in carboprost group. Our results are in accordance with the study of Yuen PH et al and Chua S et al 7,8 Bhide P et al studied the use of oxytocin, methylergometrine and carboprost during third stage of labour and found that the duration of 3 rd stage was 6 minutes 30 seconds, 5 minutes and 3 minutes 15 seconds respectively. 6 The results of our study do not match with those of the following studies.…”
Section: Discussionsupporting
confidence: 82%